Equality Content, Values and Human Rights in Socio-Humanistic Education - Skórzyńska, Izabela; Niriella, Jeeva; Stefanelli, Maria Anita; Vohra, Anupama; Singh, Jasbir (Sensus Historiae, 2025)
This unconventional text, authored by five persons - all active members of the World Center for Women’s Studies - was inspired by a series of questions posed by Izabela Skórzyńska on the theme of “Equality Content, Values, and Human Rights in Socio-Humanistic Education.” The questions were as follows: /1/ What place and role do equality content and values play in public discourse in your country and/or cultural circle? /2/ What place and role do equality content and values play in your scientific research? /3/ What problems are key to implementing equality education in your countries and/or cultural circles? /4/ How do you assess the presence of equality content, values, and human rights in academic and general education in your countries and/or cultural circles? /5/ What would you like to contribute personally to the topic addressed in the survey? The responses reflect profound insights, essential for understanding the significance of equality education across the diverse cultures of Sri Lanka, India, Italy, and Poland. This text not only contributes to self-discovery and mutual understanding of the unique characteristics of equality education - from schools and universities to social life in the distinct societies of Asia and Europe - but also attempts to capture the essence of this education. It explores the challenges it encounters, highlights areas where we, as societies and academic educators, succeed, identifies where we fall short, and examines why this topic holds personal importance for us.